Pengaruh Motivasi terhadap Kinerja Pegawai Di Badan Pertanahan Nasional Kota Depok - Arifin, Jauhary; Trihandayani, Ruri (Journal of Economics & Business UBS, 2020)
This study aims to find out how much influence motivation has on employee performance, as well as useful as a source of information and increase insight into employee motivation and performance. Testing the hypothesis that is done is to find out the significance of the influence between variables X1 (Motivation) on variavel Y (performance) by comparing between tcount and ttable then with hypothesis criteria if t count> t table then Ha is accepted Ho is rejected if thitung <ttable then Ha is rejected , Ho is accepted and compared to count and ftabel then with hypothesis criteria if f count> ftabel then Ha is accepted Ho is rejected as if f count <ftabel then Ha is rejected, Ho is accepted.The research method used is associative quantitative. Data collection methods include library research and field studies by observing and distributing questionnaires or questionnaires. As for the population in this study as many as 30 employees then the authors took a total sample of 30 respondents.The results of the calculation of simple linear regression analysis obtained Y = 0.139 + 0.958 X1 which means there is an influence of 0.958 between the motivation variable (X1) on the performance variable (Y) and by 0.139. The value of rxyÂ²x is 0.767 which means there is a strong influence between motivation, on employee performance. The result of the coefficient of determination is 58.9%. This shows that motivation and leadership style affect employee performance by 58.9% while the remaining 41.1% is influenced by other factors not examined by the author. Furthermore, based on the results of testing hypotheses using t test, and a significant value of 0.000 where the value of 0.000 <0.05 indicates that partially the Motivation variable has a significant positive effect on performance so that Ha is accepted. It can be said that there are factors that encourage to get good performance, good work quality is part of achievement motivation which is part of individual needs.